Relationship between core strength and balance ability in high school female handball and basketball players. Issue 4 (27th March 2011) - Tsukagoshi, T; Shima, Y; Nakase, J; Goshima, K; Takahashi, R; Aiba, T; Yoneda, Y; Moriyama, S; Kitaoka, K
Abstract : Background: Although a lot of reports have suggested that the core strength has an important role for the prevention of sports injuries, the relationship between core strength and balance ability is poorly documented. Objective: The purpose of this study is to examine the relationship between core strength and balance ability. Participants: 119 healthy high school female players (age: 15–16 years, handball: 49 players, basketball: 70 players) were participated in this study. Main outcome measurements: We measured endurance time of right side-bridge, left side-bridge and frontal-bridge as the core strength test (CST). To assess static balance, we used stabilometer and recorded the circumference area of the single leg standing position of 30 s. For the assessment of dynamic balance, we used star excursion balance test (SEBT). SEBT reach distances and limb lengths were examined, then the distance scores (cm) for each direction of the SEBT grid were averaged over the three trials and normalised to leg length (reach distance/leg length x 100=percentage of leg length). The normalised distances in each direction were then summed for both leg. We divided the players into three groups according to their CST score and compared them with the results of static balance and dynamic balance. Results: No significant differences were found in body size among the three groups (p<0.05). The significant difference was not found with the static balance among the CST (p<0.05). In the dynamic balance, the players with good result of CST score had significantly better results of the SEBT in frontal-bridge and left side-bridge (p<0.05). There was no significant difference in right side-bridge. Conclusion: This study showed that the core strength had certain relationship to the dynamic balance and may contribute to the prevention of sports injuries.